Advanced Calculus I
Spring 2008
Homework Solutions 1
Textbook Chapter 7
7.7 Classify each function as injective, surjective, bijective, or none of these.
(a)
f
: N
→
Z
deﬁned by
f
(
n
) =
n
2

n
Solution
This function is injective but not surjective, hence is not bijective.
Injectivity.
Suppose
n
1
,n
2
∈
N are arbitrary. Suppose
f
(
n
1
) =
f
(
n
2
)
.
We need to show
n
1
=
n
2
.
Since
f
(
n
1
) =
n
2
1

n
1
and
f
(
n
2
) =
n
2
2

n
2
, then
f
(
n
1
) =
f
(
n
2
) implies
n
2
1

n
1
=
n
2
2

n
2
(
n
2
1

n
2
2
)

(
n
1

n
2
) = 0
(
n
1

n
2
)(
n
1
+
n
2
)

(
n
1

n
2
) = 0 (
n
1

n
2
)(
n
1
+
n
2

1) = 0
This implies
n
1

n
2
= 0
or
n
1
+
n
2

1 = 0
.
Since
n
1
and
n
2
are natural numbers, then both are
≥
1 so
n
1
+
n
2
≥
2, which means
n
1
+
n
2

1
6
= 0.
Therefore
n
1

n
2
= 0 so
n
1
=
n
2
, as required. Therefore
f
is injective.
Surjectivity.
We show that there exists
k
∈
Z such that
f
(
n
)
6
=
k
for all
n
∈
N.
Choose
k
=

1. Clearly
k
=

1
∈
Z. Suppose
n
is an arbitrary natural number. Then
f
(
n
) =
n
2

n
=
n
(
n

1)
≥
0
,
so
f
(
n
)
6
=

1 =
k
, as required.
Thus
f
is not surjective.
(d)
f
: [3
,
∞
)
→
[5
,
∞
) deﬁned by
f
(
x
) = (
x

3)
2
+ 5.
Solution
This function is both injective and surjective, hence is bijective.
Injectivity.
Suppose
x
1
,x
2
∈
[3
,
∞
) are arbitrary. Suppose
f
(
x
1
) =
f
(
x
2
)
.
We need to show
x
1
=
x
2
.
Since
f
(
x
1
) =
f
(
x
2
), then
(
x
1

3)
2
+ 5 = (
x
2

3)
2
+ 5 (
x
1

3)
2
= (
x
2

3)
2

x
1

3

=

x
2

3

upon taking square roots of both sides of the equality. Since
x
1
,x
2
≥
3, then
x
1

3
≥
0 and
x
2

3
≥
0, so

x
1

3

=
x
1

3 and

x
2

3

=
x
2

3. The above equality then simpliﬁes to
x
1

3 =
x
2

3 and so
x
1
=
x
2
. Therefore
f
is injective.
Surjectivity.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
This is the end of the preview.
Sign up
to
access the rest of the document.
 Spring '08
 QIAN
 Calculus, Inverse function, C. From Theorem

Click to edit the document details